2021
DOI: 10.7717/peerj.10909
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training with different repetition duration to failure: effect on hypertrophy, strength and muscle activation

Abstract: Background This study investigated the effects of two 14-week resistance training protocols with different repetition duration (RD) performed to muscle failure (MF) on gains in strength and muscle hypertrophy as well as on normalized electromyographic (EMG) amplitude and force-angle relationships. Methods The left and right legs of ten untrained males were assigned to either one of the two protocols (2-s or 6-s RD) incorporating unilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Also, a potentiometer, coupled to the rotational axis of the mechanical arm of the knee extension machine, provided real-time biofeedback on a computer screen as to the ROM excursed by each volunteer. The use of a potentiometer to analyze the ROMs excursed during tests and training were described in previous studies of our group (Diniz et al, 2020;Lacerda et al, 2021).…”
Section: Pre-training Sessionmentioning
confidence: 99%
“…Also, a potentiometer, coupled to the rotational axis of the mechanical arm of the knee extension machine, provided real-time biofeedback on a computer screen as to the ROM excursed by each volunteer. The use of a potentiometer to analyze the ROMs excursed during tests and training were described in previous studies of our group (Diniz et al, 2020;Lacerda et al, 2021).…”
Section: Pre-training Sessionmentioning
confidence: 99%
“…Finally, muscular cross-sectional area (CSA) adaptations were extensively studied in both population groups. The highest values were recorded in the training cadences with ECC MAD equal to CON MAD (+3.4-27.0%) in untrained subjects (5,7,34,55,57) with the higher values in cadence 1-2/0/1-2/0 (55) and those in which CON MAD was greater than ECC MAD (+4.3-25.8%) (7,19) with the higher values in cadence 2/0/6/0 (19).…”
Section: Resultsmentioning
confidence: 89%
“…The interventions in the analyzed studies comprised a total repetition MAD of between 4 and 14 seconds (1,5,7,19,34,47,48,55,57,58,60,61), with most of the investigations with a total repetition MAD of less than 7 seconds (1,5,7,34,47,48,57,58,60,61). These training prescriptions are consistent with those in the study by Schoenfeld et al (54), who found muscle hypertrophic improvements are similar when training with a total repetition MAD of between 0.5 and 8 seconds, as long as muscle failure is reached.…”
Section: Muscle Hypertrophymentioning
confidence: 99%
“…In other words, recent studies have reported that instead of the training volume that was previously considered important, the impulse (training load × muscular exertion duration) during training might be an important factor. However, a previous study that compared the training effects of two protocols with the same training load and different impulses demonstrated no difference in the training effect 19) ; thus, further studies on impulse are necessary.…”
Section: Introductionmentioning
confidence: 93%